Hinkley criterion applied to detection and location of burn in grinding process - Távora, Carine G. [UNESP]; Aguiar, Paulo R. [UNESP]; Castro, Bruno A. [UNESP]; Alexandre, Felipe A. [UNESP]; Andreoli, André L. [UNESP]; Bianchi, Eduardo C. [UNESP] (Springer Nature, 2021)
Grinding is a machining process widely applied in the manufacture of products that require low tolerance and high-dimensional accuracy. One of the most critical issues in this manufacturing process is the material burn phenomenon, which can lead the part to a total failure. Therefore, monitoring burn in the grinding process is crucial to ensure a high level of quality, productivity, and repeatability of industrial processes. This article presents a new non-destructive approach for the onset location of burn in the SAE 1045 steel, aiming to develop a reliable and robust grinding monitoring system as an alternative to invasive methods. An experimental investigation was conducted by using low-cost piezoelectric diaphragms and feature extraction of the signals through Hinkley criterion. By comparing to the traditional and invasive tests such as microhardness measurements and metallographic analysis, it was concluded that the Hinkley criterion has a high effectiveness and potential to locate the onset of burn, since the error of the location was less than 4%.
Keywords: Grinding; Hinkley criterion; Manufacturing processes; Nondestructive testing; Piezoelectric transducer